Economy and environment (2013)
In certain academic, political, social, and environmental scenes it is declared that the dominant economic model or the concepts that integrate it are responsible for which the economic well-being implies ecological malaise. Starting off of this assumption, a form to include/understand the causes and to contribute to the problematic solution of the environmental one is to reveal in what they consist, in what terms raise the relation man-environment, the proposals that include the environmental dimension in the field of the economy, and if like the environmental theories, go to the ethics like suitable factor to diminish the negative externalities generated in the atmosphere by the economic activity